Боргові зобов’язання підприємств: процедура банкрутства та визнання вимог кредиторів - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia (My University, 2018)
UK: В статті розглянуто особливості оперативного погашення боргових зобов’язань підприємств через процедуру банкрутства, із встановленням чіткого механізму визнання вимог кредиторів. Проведено порівняльний аналіз індексу відповідності платоспроможності вітчизняних підприємств, країн Європи і Центральної Азії та країн ОЕСР у рейтингу Doing Business. Визначено масштаби кризових явищ та динаміку провадження справ про банкрутство, ефективності процедур відновлення платоспроможності або ліквідації боржника в Ук-раїні. EN: The article deals with the peculiarities of the operational repayment of debt obligations of enterprises through bankruptcy procedure, with the establishment of a clear mechanism for recognizing the claims of creditors. The interdependence of financial interests of debtor companies and lenders in the countries of Europe and Ukraine are con-sidered. A comparative analysis of the compliance index of solvency of domestic enterprises, countries of Europe and Central Asia and OECD countries in the Doing Business rating is carried out. The scale of crisis phenomena and dy-namics of bankruptcy proceedings, efficiency of solvency restoration procedures or liquidation of a debtor in Ukraine are determined. It is grounded that the regulatory framework for restoring the debtor solvency or recognizing it as a bankrupt and the provisions on regulating the rules of criminal and economic law have problems with the implementa-tion of the procedure for the reorganization of insolvent enterprises and the participation of creditors in the process of their liquidation or restructuring. The existence of the practice of abuse of the bankruptcy institute by both enterprises and lenders has been proved, as a result of attempts to evade payment of its debt obligations and the taking over of the debtor’s property in a crisis condition by controlling the committee of creditors and the arbitration manager. The priority directions of financial rehabilitation of enterprises, in particular, due to the use of internal mechanisms of liquidity restoration, reduction of all kinds of debts, improvement of working capital structure, improvement of bankruptcy procedure with recognition of claims of creditors, are determined.
Business liabilities of enterprises: bankruptcy procedure and recognition of creditors claims
Keywords: банкрутство; вимоги кредиторів; неплатоспроможність підприємства; фінансова криза; санація; bankruptcy; creditors’ claims; the enterprise insolvency; financial crisis; sanitation